Concept of Suicide: Neurophysiological/Genetic Theories and Possible Oxytocin Relevance - Padurariu, M.; Prepelita, R.; Ciobica, A.; Dobrin, R.; Timofte, D.; Stefanescu, C.; Chirita, R. (Нейрофизиология, 2016)
The suicidal behavior is regarded as the act by which a person seeks to take his life, being aware of the consequences of his action. In our review, besides describing the main introductory aspects for the concept of suicide, we focus our attention on the main neurophysiological and genetical mechanisms relevant for this extremely difficult to manage and controversial behavior. Moreover, considering the latest interests in the current literature on the relevance of central oxytocin to various superior cognitive behaviors, we will also make a short description on how important effects of oxytocin could be in the context of suicidal behavior.